Effect of two weeks of sprint interval training combined with omega-3 consumption on serum levels of Irisin, BDNF and Lipid profile in overweight girls - Fatemeh Dinarvandi; Hadis Sharifi; Vahid Valipour Dehnou; Amir Khosravi (Mashhad University of Medical Sciences, 2020)
Introduction: Severe interval training is an effective way to improve cognitive function, cardiovascular health and body weight reduction; so far, the combined effect of this type of exercise with omega-3 supplementation in overweight girls has not been studied. Therefore, this study was performed with aim to evaluate the effect of two weeks of sprint interval training (SIT) combined with omega-3 consumption on serum levels of Irisin, BDNF and Lipid profile in overweight girls. Methods: This randomized clinical trial study was performed in 2019 on 15 students of Lorestan university with BMI>25 kg/m2. Subjects were divided into two groups: training-placebo and training-supplement. Subjects participated in a 2-week SIT protocol (3 sessions per week). The participants in the training-supplement group received an omega-3 tablet (1000 mg) and training-placebo group received glucose tablet (1 gram) each day for two weeks. Serum levels of irisin, BDNF and lipid profile were measured at fasting 24 hours before and after the training protocol. Data were analyzed by SPSS software (version 25) and paired t-test and covariance test. P<0.05 was considered statistically significant. Results: The results of the study showed a significant increase in serum levels of irisin and BDNF in both groups (p<0.05). However, in the training-supplement group, serum levels of LDL and cholesterol also decreased (p<0.05). Also, the results of covariance test showed no significant difference between the two groups in all variables (p˃0.05). Conclusion: Sprint interval training for two weeks with and without omega 3 consumption increases serum levels of irisin and BDNF in overweight girls, and omega-3 consumption combined with this type of training, also reduces serum levels of LDL and cholesterol.